Discovery and Photoisomerization of New Pyrrolosesquiterpenoids Glaciapyrroles D and E, from Deep-Sea Sediment Streptomyces sp. - Ko, Keebeom; Seong-Hwan Kim; Park, Subin; HAN, HWA SEUNG; Lee, Jae Kyun; Cha, Jin Wook; Hwang, Sunghoon; Choi, Ki Young; Song, Yoon-Jae; Nam, Sang-Jip; Shin, Jongheon; Nam, Seung-Il; et al. (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
Two new pyrrolosesquiterpenes, glaciapyrroles D (1) and E (2) were discovered along with the previously reported glaciapyrrole A (3) from Streptomyces sp. GGS53 strain isolated from deep-sea sediment. This study elucidated the planar structures of 1 and 2 using nuclear magnetic resonance (NMR), mass spectrometry (MS), ultraviolet (UV), and infrared (IR) spectroscopic data. The absolute configurations of the glaciapyrroles were determined by Mosher’s method, circular dichroism spectroscopy, and X-ray crystallography. Under 366 nm UV irradiation, the glaciapyrroles were systematically converted to the corresponding photoglaciapyrroles (4？6) via photoisomerization, resulting in the diversification of the glaciapyrrole family compounds. The transformation of the glaciapyrrole Z to E isomers occurred in a 1:1 ratio, based on virtual validation of the photoisomerization of these olefinic compounds by 1H-NMR spectroscopy and liquid chromatography/mass spectrometry (LC/MS) analysis. Finally, when encapsulated in poly(lactic-co-glycolic acid) nanoparticles, glaciapyrrole E and photoglaciapyrrole E displayed significant inhibitory activity against influenza A virus. This is the first report of antiviral effects from glaciapyrrole family compounds, whose biological functions have only been subjected to limited studies so far.